Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.9778/cmajo.20190090
|View full text |Cite
|
Sign up to set email alerts
|

Gender and academic promotion of Canadian general surgeons: a cross-sectional study

Abstract: ender disparity in academic promotion has been investigated among physicians in the United States. 1,2 After age, experience, specialty and research productivity are accounted for, women are less likely than men to be full professors. 2 Markers suggestive of inequity, defined as a lack of fairness, in academia also exist among Canadian professors, with women representing only 27.6% of full professors 3 and receiving on average $10 263 less than men in annual salary. 4 In addition, women account for just 12% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
4
21
1
Order By: Relevance
“…This study joins others among surgical subspecialties in highlighting ongoing gender disparity with regards to women surgeons within academia [ 32 37 , 40 , 41 , 43 48 , 51 , 52 , 54 – 58 , 64 ]. While our investigation highlights the current Canadian environment, the themes of ongoing gender disparity are not isolated to this country; with specific studies noting that inequities exist in Plastic Surgery, Neurosurgery and General surgery across North America, the EU and Oceania [ 39 , 45 , 46 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This study joins others among surgical subspecialties in highlighting ongoing gender disparity with regards to women surgeons within academia [ 32 37 , 40 , 41 , 43 48 , 51 , 52 , 54 – 58 , 64 ]. While our investigation highlights the current Canadian environment, the themes of ongoing gender disparity are not isolated to this country; with specific studies noting that inequities exist in Plastic Surgery, Neurosurgery and General surgery across North America, the EU and Oceania [ 39 , 45 , 46 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 61%
“…There is very limited data examining the gender distribution and achievements of Canadian surgeons. Of the existing Canadian research, it has been shown that women surgeons are less likely to ascend to higher ranks of academic faculty or to leadership positions, and they make statistically significantly less money than their men colleagues [ 41 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 88 ] High income United States Retrospective review Not reported 2020 Gender and academic promotion of Canadian general surgeons: a cross-sectional study. [ 89 ] High income Canada Cross-sectional analysis n = 405 (111/294) 27% Not reported 2020 Gender Disparities Among Burn Surgery Leadership. [ 90 ] High income United States Cross-sectional analysis n = 581 (58/523) 10% No funding 2020 Gender Disparity Among Surgical Peer-Reviewed Literature.…”
Section: Resultsmentioning
confidence: 99%
“…Gender and ethnicity based disparities in medicine have been documented for over 30 years 8. Disparities in promotion,9 compensation,1011 discrimination,1112 and harassment13 that disadvantage women and racialised physicians have been found in every setting and specialty where such inequities have been studied.…”
Section: Lack Of Diversity Perpetuates Lack Of Diversitymentioning
confidence: 99%